1983
DOI: 10.1111/j.2042-3306.1983.tb01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and haematological effects of phenylbutazone in horses

Abstract: Summary Five matched pairs of horses were used to investigate the effects of phenylbutazone on a range of physiological, biochemical and haematological variables. The drug was given by mouth daily for 15 consecutive days at the manufacturer's recommended dose rates to one group of horses (Group A); the second group (Group B) received equivalent doses of a placebo. For some of the measured parameters, significant changes were recorded in both groups, indicating background instability. Significant decreases in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…When phenylbutazone was given to three-to-10-monthold foals (10 mg/kg bwt daily for 12 to 42 days) nine out of 10 showed no clinical signs although endoscopic and radiographic ante mortem and subsequent post mortem examinations showed a high incidence of ulceration (Traub et al 1983a). In view of the authors' experience with phenylbutazone in aged horses (Lees et al 1983a) it would seem worthwhile examining the effect of age on susceptibility to the toxic effects of the drug. Although Snow et al(1981b) have concluded that there were breed differences in the susceptibility of horses to the toxic effects of phenylbutazone, and that pony breeds are more susceptible than Thoroughbreds, it is possible that the lack of clinical signs of toxicity in Thoroughbreds could have been because of the lower doses of phenylbutazone given (8.2 mg/kg bwt daily in two doses for 13 days compared with 12 mg/kg bwt fed in two equal doses to ponies for eight to 10 days).…”
Section: Phenylbutazonementioning
confidence: 99%
“…When phenylbutazone was given to three-to-10-monthold foals (10 mg/kg bwt daily for 12 to 42 days) nine out of 10 showed no clinical signs although endoscopic and radiographic ante mortem and subsequent post mortem examinations showed a high incidence of ulceration (Traub et al 1983a). In view of the authors' experience with phenylbutazone in aged horses (Lees et al 1983a) it would seem worthwhile examining the effect of age on susceptibility to the toxic effects of the drug. Although Snow et al(1981b) have concluded that there were breed differences in the susceptibility of horses to the toxic effects of phenylbutazone, and that pony breeds are more susceptible than Thoroughbreds, it is possible that the lack of clinical signs of toxicity in Thoroughbreds could have been because of the lower doses of phenylbutazone given (8.2 mg/kg bwt daily in two doses for 13 days compared with 12 mg/kg bwt fed in two equal doses to ponies for eight to 10 days).…”
Section: Phenylbutazonementioning
confidence: 99%
“…However, urinalysis did not show significant increases of protein in the urine at the time of peripheral hypoproteinaemia. A protein‐losing gastroenteropathy has been documented in toxicity studies of phenylbutazone in the horse ( Snow et al ., 1979 ; Lees et al ., 1983 ; MacKay et al ., 1983 ). Faecal losses of plasma albumin, using a 51Cr‐labelled plasma albumin technique, were shown in ponies given large doses of phenylbutazone (8–12 mg/kg for 8 days) ( Snow et al ., 1981 ).…”
Section: Discussionmentioning
confidence: 99%
“…23 In horses, reports of hematologic effects of phenylbutazone are mixed. 14,15,17,19,24,26 Decreased albumin concentration, attributed to gastrointestinal loss, 14,17,19,24 and neutropenia, associated with a much higher dose of phenylbutazone administered over a longer time, were reported. 19 Hence, although it is possible that phenylbutazone had toxic effects on granulopoiesis in this horse, it was considered unlikely.…”
Section: Discussionmentioning
confidence: 99%